Investigations of Low-Symmetrical Tetraaryltetrabenzoporphyrins Produced by Mixed Condensation Reactions - Ruppel, Michael; Gazetas, Lampros-Pascal; Lungerich, Dominik; Hampel, Frank; Jux, Norbert (Journal of Organic Chemistry, 2020)
Within the past decade, tetraaryltetrabenzoporphyrins (TATBPs) have gained rising attention due to their potential in various fields of materials science and medicinal chemistry. However, this class of compounds still lacks in structural diversity, especially in the case of low-symmetrical compounds. Herein, mixed condensations were utilized to generate TATBPs with different substituents either in the meso-positions or the periphery of the macrocycle with total yields of 55-58%. The separation of crude mixtures was achieved by feasible chromatographic purification. The influence of symmetry on the electronic properties of TATBPs was studied by optical spectroscopy, electrochemistry, and X-ray diffraction.
CRIS-Team WoS Importer:2020-07-17